PENAPISAN AKTIVITAS LIPOLITIK SEPULUH BIAKAN Rhizopus KOLEKSIUICC (UNIVERSITY OF INDONESIA CULTURE COLLECTION) - Inu Yuyun Lusini; Wibowo Mangunwardoyo 'ET; Indrawati Gandjar (BERITA BIOLOGI, 2009)
Ten Rhizopus were screened for their extracellular lipolytic activity. All strains showed lipolytic activity with diffferent activities.R. microsporus var. rhizopodiformis (Cohn) Scipper & Stalpers UICC 520 (4.52 unit/ml) and R. microsporus var. oligosporus UICC 550 (2.58 unit/ml) showed a high lipolytic activity in screening medium containing 5% pepton and 1% glucose (b/v) without a lipid substrate after 24 hours of incubation at room temperature.